A method for preparing porous starch with high oil absorption rate

Through the use of composite enzymes, sodium phosphate, and methyl acrylic ethyl acetate during the preparation of porous starch, it improved the oil absorption of porous starch, solved the problem of insufficient porous starch oil absorption, and realized the high oil absorption rate. The effect of higher stability.

CN116041623BActive Publication Date: 2025-01-28DONGGUAN DONGMEI FOOD +1

Patent Information

Application Number
CN202211130796.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-01-28
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

The oil absorption of existing porous starch is insufficient and it is difficult to meet the high requirements of environmentally friendly and energy-saving materials. It is necessary to increase the specific surface area of ​​large starch, increase the pore size, increase the degree of crosslinking and grafting rate to enhance oil absorption.

Method used

Use a specific proportional composite enzyme to reduce the accumulation density, reference sodium sodium phosphate to increase the degree of cross -linking, increase the oil absorption rate through the pruning reaction of methacryal ethyl acetate, and use the ratio of hydrogen peroxide and sulfur dioxide to increase the branching rate. And branches efficiency.

Benefits of technology

It significantly increases the oil absorption rate of porous starch, enhances its absorption of oil, and improves product stability and industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003850199500000091
    Figure BDA0003850199500000091
  • Figure BDA0003850199500000092
    Figure BDA0003850199500000092
  • Figure BDA0003850199500000093
    Figure BDA0003850199500000093
Patent Text Reader

Abstract

The invention relates to a method for preparing porous starch with high oil absorption rate, and belongs to the technical field of starch production. The method comprises the following preparation steps: weighing a cross-linked body, sequentially adding ammonium ferrous sulfate solution, deionized water, ethyl methacrylate, thiourea oxide and hydrogen peroxide solution, controlling the rotation speed, mechanically stirring, passing nitrogen, controlling the temperature for reaction, washing with water after the reaction is completed to obtain grafted porous starch, placing the grafted porous starch in an extractor for acetone extraction for 24-26 hours, taking out, drying, and obtaining a porous starch with high oil absorption rate; the method adopts a composite enzyme of a specific proportion to reduce the bulk density, introduces sodium trimetaphosphate to increase the cross-linking degree, and reduces the sedimentation volume; a porous network structure surface formed by sodium trimetaphosphate and the porous starch after enzymolysis absorbs ethyl methacrylate into the interior of particles, and a specific ratio of hydrogen peroxide and thiourea oxide increases the grafting rate and grafting efficiency of ethyl methacrylate, thereby increasing the oil absorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of starch production, and in particular relates to a method for preparing porous starch with high oil absorption rate. Background Art

[0002] Porous starch refers to a modified starch with a honeycomb porous structure obtained by hydrolyzing starch granules at a certain temperature. The surface of porous starch has many small holes with a diameter of about 1 μm and has a certain particle strength. It has abundant raw material sources, relatively low price cost, and good industrial development value.

[0003] The existing porous starch on the market already has a certain oil absorption capacity, but with the rapid development of environmentally friendly and energy-saving materials, people have higher and higher requirements for porous starch. General porous starch is still far from meeting the requirements of actual use. The oil absorption ultimately depends on the adsorption effect produced on the surface and porous interior of the porous starch. Therefore, the prepared porous starch must maintain the integrity of the particles and have as many holes as possible on the particles to improve the oil absorption. In addition, during the preparation process, the degree of cross-linking and the grafting rate also have a great influence on the product. Therefore, studying how to increase the specific surface area of ​​large starch, increase the pore size, and increase the degree of cross-linking and grafting rate to further enhance the oil absorption rate has become an urgent problem to be solved. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing porous starch with high oil absorption rate, wherein a composite enzyme in a specific ratio is used to reduce the bulk density, sodium trimetaphosphate is used to increase the cross-linking degree, and the sedimentation volume is reduced; a porous network structure surface formed by sodium trimetaphosphate and porous starch after enzymatic hydrolysis absorbs ethyl methacrylate into the interior of particles, and a specific ratio of hydrogen peroxide and thiourea oxide is used to increase the grafting rate and grafting efficiency of ethyl methacrylate, thereby increasing the oil absorption rate.

[0005] The technical problem to be solved by the present invention is to increase the specific surface area of ​​large starch, enlarge the pore size, and improve the cross-linking degree and grafting rate to further enhance the oil absorption rate.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing porous starch with high oil absorption rate comprises the following steps: weighing a cross-linked body, sequentially adding 0.1 mol / L ammonium ferrous sulfate solution, deionized water, ethyl methacrylate, oxidized thiourea and 0.003 mol / L hydrogen peroxide solution, controlling the rotation speed, mechanically stirring evenly, passing nitrogen for 0.5-1h, controlling the temperature to react, washing with water after the reaction is completed to obtain a grafted porous starch, placing the grafted porous starch in an extractor to extract with acetone for 24-26h, taking out and drying to obtain a porous starch with high oil absorption rate;

[0008] Passing nitrogen is conducive to expelling oxygen from the bottle; ethyl methacrylate can be absorbed into the interior of the particles by the network structure surface and porous strong adsorption force formed by sodium trimetaphosphate and the porous starch after enzymatic hydrolysis, and is tightly combined with the porous starch for grafting, which is more stable and not easy to detach, further improving the porous starch's adsorption capacity for oil and increasing the oil absorption rate; hydrogen peroxide acts as an initiator in the reaction system to generate free radicals, which trigger the grafting copolymerization of porous starch and ethyl methacrylate, generating a large number of active centers, which start polymerization and allow the monomer to be smoothly grafted onto the porous starch to produce branches; oxidized thiourea and ferrous ions form a reduction system, reducing the trivalent iron ions generated in the system to divalent iron ions, which re-participate in the reaction, rapidly increasing the speed of the grafting reaction and improving the effect of the grafting reaction.

[0009] Furthermore, the weight ratio of the cross-linked body, ammonium ferrous sulfate solution, deionized water, ethyl methacrylate, oxidized thiourea and hydrogen peroxide solution is 4-6: 0.03-0.05: 130-160: 8-9: 0.5-0.8: 0.02-0.03.

[0010] Furthermore, the rotation speed is 30-50 rpm, the temperature is 48-52° C., and the reaction time is 1-1.2 h; preferably, in order to increase the active centers on the porous starch skeleton, accelerate molecular diffusion, and speed up chain initiation and chain growth, the temperature is set to 51° C.

[0011] Furthermore, the extractor is a Soxhlet extractor.

[0012] Furthermore, the cross-linked body is prepared by the following method:

[0013] Step S1, stirring and mixing wheat starch and a buffer solution to obtain a mixed solution, preheating, adding a composite enzyme, stirring and enzymolyzing under controlled temperature, adding hydrochloric acid to adjust the pH to 3 after the reaction is completed, mechanically stirring and mixing to react, neutralizing the hydrochloric acid in the solution with NaOH after the reaction is completed, vacuum filtering after the neutralization is completed, washing with ethanol and water, and drying at normal pressure to obtain enzymolyzed starch;

[0014] Step S2, the enzymatic starch obtained in step S1, deionized water and sodium sulfate are mixed and stirred evenly, the pH is adjusted to 11 with sodium hydroxide, stirred in a water bath, sodium trimetaphosphate is added for mixed reaction, the pH is adjusted to 6 with hydrochloric acid, washed with water, dried and crushed to obtain a cross-linked body.

[0015] Furthermore, in step S1, the dosage ratio of wheat starch, buffer solution and complex enzyme is 30-60 g: 170-190 mL: 3-5 g.

[0016] Furthermore, the buffer in step S1 is sodium dihydrogen phosphate-citric acid with a pH of 6.0, and the composite enzyme is saccharifying enzyme: β-amylase = 2:1. The composite enzyme causes porous starch to produce a large number of holes that penetrate from the surface to the center of the particles, and channels are formed inside the starch particles, which have a larger specific surface area and a higher porosity, thereby reducing the packing density.

[0017] Furthermore, the preheating environment in step S1 is preheating in a water bath at 47-51°C for 9-13 minutes, the temperature of enzymatic hydrolysis stirring is 47-51°C, the reaction time is 10-15 minutes, and the temperature of atmospheric pressure drying is 35-45°C, and the time is 22-26 hours.

[0018] Furthermore, in step S2, the dosage ratio of the enzymatically hydrolyzed starch, deionized water, sodium sulfate and sodium trimetaphosphate is 20-40g: 100-120mL: 12-16g: 2-4g. The sodium trimetaphosphate is cross-linked with the porous starch after enzymatic hydrolysis, the molecular chains are broken, and more hydroxyl groups are exposed to form a network structure, which enhances the strength of the hydrogen bonds and inhibits the swelling of the cross-linked porous starch particles, thereby reducing the sedimentation volume.

[0019] Furthermore, in step S2, the temperature of the water bath stirring is 42-48° C., and the mixing reaction time is 1-1.5 h.

[0020] Beneficial effects of the present invention:

[0021] (1) The use of a composite enzyme with a ratio of saccharifying enzyme to β-amylase of 2:1 significantly reduces the bulk density, and the use of sodium trimetaphosphate as a cross-linking agent greatly reduces the sedimentation volume; the reduction in bulk density is due to the fact that after enzymatic hydrolysis, the porous starch forms a hollow structure or pores inside, and channels are formed inside the starch granules, and the depth of the pores and channels varies. Therefore, the porous starch will have a larger specific surface area, a higher porosity, and a lower bulk density; and the reduction in sedimentation volume is due to the fact that the content of amylose in the porous starch is very low and it is easy to expand when heated. On the other hand, after enzymatic hydrolysis, the molecular chain of the porous starch breaks, and more hydroxyl groups are exposed, which increases the expansion force of the starch. With the increase in the amount of cross-linking agent added, the cross-linking degree between the porous starch and sodium trimetaphosphate is enhanced, the strength of the hydrogen bond is enhanced, and the swelling of the cross-linked porous starch particles is inhibited, so the sedimentation volume decreases.

[0022] (2) Ethyl methacrylate is added. Ethyl methacrylate is firmly adsorbed in a network structure formed by sodium trimetaphosphate and porous starch for grafting. As the reaction time increases, the porous starch after enzymatic hydrolysis has more pores inside and has honeycomb-shaped holes with relatively large pore sizes on the surface. Therefore, the adsorption of ethyl methacrylate does not only rely on surface adsorption, but more on the strong adsorption capacity of the porous structure to adsorb the target substance, that is, the surface adsorption of atomic groups is combined with the adsorption of holes. After adsorption, most of the adsorbed substances enter the interior of the porous starch particles through the holes on the surface of the porous starch particles, and are tightly combined with the porous starch. The stability is higher and it is not easy to detach. This tight adsorption force further improves the adsorption capacity of the porous starch for oil, so the oil absorption rate will increase.

[0023] (3) Hydrogen peroxide is used as an initiator of the reaction system, and its function is to generate primary free radicals to initiate the graft copolymerization of porous starch and ethyl methacrylate. The key to the free radical graft copolymerization reaction is to generate a large number of active centers in the porous starch, and the reaction monomers start to polymerize from the active centers, so that the monomers are smoothly grafted onto the porous starch to generate branches; the present invention also introduces thiourea oxide, which, on the one hand, forms a reduction system with ferrous ions, reduces the trivalent iron ions generated in the system to divalent iron ions, re-participates in the reaction, and increases the free radical concentration in the reaction system; on the other hand, it can also generate free radicals to participate in the reaction, quickly increase the speed of the graft reaction, and improve the effect of the graft reaction; the specific ratio of hydrogen peroxide and thiourea oxide increases the grafting rate and grafting efficiency of ethyl methacrylate and increases the oil absorption rate. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A method for preparing porous starch with high oil absorption rate comprises the following steps:

[0027] Step S1, 30g wheat starch and 170mL sodium dihydrogen phosphate-citric acid buffer solution with pH=6.0 were stirred and mixed to obtain a mixed solution, the temperature was controlled at 49°C, and the solution was preheated in a water bath for 9min, 3g of a composite enzyme of saccharifying enzyme: β-amylase=2:1 was added, the temperature was controlled at 49°C for stirring and enzymolysis, and after the reaction was completed, hydrochloric acid was added to adjust the pH to 3, mechanical stirring and mixing were performed, and the reaction was performed for 13min, and the hydrochloric acid in the solution was neutralized with NaOH. After the neutralization was completed, the solution was vacuum filtered, washed with ethanol and water, and dried at 40°C under normal pressure for 24h to obtain enzymolyzed starch;

[0028] Step S2, weighing 20g of enzymatic starch obtained in step S1, 100mL of deionized water and 12g of sodium sulfate, mixing and stirring evenly, adjusting the pH to 11 with sodium hydroxide, stirring in a water bath at 45°C, adding 2g of sodium trimetaphosphate and mixing for 1h, adjusting the pH to 6 with hydrochloric acid, washing, drying and crushing to obtain a cross-linked body;

[0029] Step S3, weighing 4 parts by weight of the cross-linked body obtained in step S2, adding 0.03 parts by weight of 0.1 mol / L ammonium ferrous sulfate solution, 130 parts by weight of deionized water, 8 parts by weight of ethyl methacrylate, 0.5 parts by weight of 0.003 mol / L thiourea oxide and 0.02 parts by weight of hydrogen peroxide solution into a four-necked flask in sequence, controlling the rotation speed to 35 rpm, mechanically stirring evenly, passing nitrogen for 1 hour, and controlling the temperature to 51° C. for reaction, washing with water after the reaction is completed to obtain a grafted porous starch, placing the grafted porous starch in a Soxhlet extractor and extracting it with acetone for 25 hours, taking it out and drying it to obtain a porous starch with high oil absorption rate.

[0030] Example 2

[0031] A method for preparing porous starch with high oil absorption rate comprises the following steps:

[0032] Step S1, 45g wheat starch and 180mL sodium dihydrogen phosphate-citric acid buffer solution with pH=6.0 were stirred and mixed to obtain a mixed solution, the temperature was controlled at 49°C, and the solution was preheated in a water bath for 11min, 4g of a complex enzyme of saccharifying enzyme: β-amylase=2:1 was added, the temperature was controlled at 49°C for stirring and enzymolysis, and after the reaction was completed, hydrochloric acid was added to adjust the pH to 3, mechanical stirring and mixing were performed, and the reaction was performed for 13min, and the hydrochloric acid in the solution was neutralized with NaOH. After the neutralization was completed, vacuum filtration was performed, the solution was washed with ethanol and water, and the solution was dried at 40°C under normal pressure for 24h to obtain enzymolyzed starch;

[0033] Step S2, weighing 30g of the enzymatic starch obtained in step S1, 110mL of deionized water and 14g of sodium sulfate, mixing and stirring evenly, adjusting the pH to 11 with sodium hydroxide, stirring in a water bath at 45°C, adding 3g of sodium trimetaphosphate and mixing for 1h, adjusting the pH to 6 with hydrochloric acid, washing, drying and crushing to obtain a cross-linked body;

[0034] Step S3, weighing 5 parts by weight of the cross-linked body obtained in step S2, adding 0.04 parts by weight of 0.1 mol / L ammonium ferrous sulfate solution, 145 parts by weight of deionized water, 8.5 parts by weight of ethyl methacrylate, 0.65 parts by weight of 0.003 mol / L thiourea oxide and 0.025 parts by weight of hydrogen peroxide solution into a four-necked flask, controlling the rotation speed to 35 rpm, mechanically stirring evenly, passing nitrogen for 1 hour, and controlling the temperature to 51° C. for reaction, washing with water after the reaction is completed to obtain a grafted porous starch, placing the grafted porous starch in a Soxhlet extractor and extracting it with acetone for 25 hours, taking it out and drying it to obtain a porous starch with high oil absorption rate.

[0035] Example 3

[0036] A method for preparing porous starch with high oil absorption rate comprises the following steps:

[0037] Step S1, 60g wheat starch and 190mL sodium dihydrogen phosphate-citric acid buffer solution with pH=6.0 were stirred and mixed to obtain a mixed solution, the temperature was controlled at 49°C, and the solution was preheated in a water bath for 13min, 5g of a composite enzyme of saccharifying enzyme: β-amylase=2:1 was added, the temperature was controlled at 49°C for stirring and enzymolysis, and after the reaction was completed, hydrochloric acid was added to adjust the pH to 3, mechanical stirring and mixing were performed, and the reaction was performed for 13min, and the hydrochloric acid in the solution was neutralized with NaOH. After the neutralization was completed, vacuum filtration was performed, the solution was washed with ethanol and water, and the solution was dried at 40°C under normal pressure for 24h to obtain enzymolyzed starch;

[0038] Step S2, weigh 40g of enzymatic starch obtained in step S1, 120mL of deionized water and 16g of sodium sulfate, mix and stir evenly, adjust the pH to 11 with sodium hydroxide, control the temperature at 45°C for stirring in a water bath, add 4g of sodium trimetaphosphate and mix for 1h, adjust the pH to 6 with hydrochloric acid, wash, dry and crush to obtain a cross-linked body.

[0039] Step S3, weighing 6 parts by weight of the cross-linked body obtained in step S2, adding 0.05 parts by weight of 0.1 mol / L ammonium ferrous sulfate solution, 160 parts by weight of deionized water, 9 parts by weight of ethyl methacrylate, 0.8 parts by weight of 0.003 mol / L thiourea oxide and 0.03 parts by weight of hydrogen peroxide solution to a four-necked flask, controlling the rotation speed to 35 rpm, mechanically stirring evenly, passing nitrogen for 1 hour, controlling the temperature to 51° C. for reaction, washing with water after the reaction is completed to obtain a grafted porous starch, placing the grafted porous starch in a Soxhlet extractor and extracting with acetone for 25 hours, taking out and drying to obtain a porous starch with high oil absorption rate

[0040] Comparative Example 1

[0041] Compared with Example 2, a composite enzyme of saccharifying enzyme:β-amylase=1:1 was added in step S1, and the remaining steps and parameters were the same.

[0042] Comparative Example 2

[0043] Compared with Example 2, a composite enzyme with a ratio of saccharifying enzyme to β-amylase of 3:1 was added in step S1, and the remaining steps and parameters were the same.

[0044] Comparative Example 3

[0045] Compared with Example 2, a composite enzyme of saccharifying enzyme:β-amylase=1:2 was added in step S1, and the remaining steps and parameters were the same.

[0046] Comparative Example 4

[0047] Compared with Example 2, a composite enzyme of saccharifying enzyme:β-amylase=1:3 was added in step S1, and the remaining steps and parameters were the same.

[0048] Comparative Example 5

[0049] Compared with Example 2, the amount of sodium trimetaphosphate added in step S2 is 1 g, and the remaining steps and parameters are the same.

[0050] Comparative Example 6

[0051] Compared with Example 2, the amount of sodium trimetaphosphate added in step S2 is 5 g, and the remaining steps and parameters are the same.

[0052] Comparative Example 7

[0053] Compared with Example 2, 7 parts by weight of ethyl methacrylate are added in the preparation of a porous starch with high oil absorption rate, and the remaining steps and parameters are the same.

[0054] Comparative Example 8

[0055] Compared with Example 2, 10 parts by weight of ethyl methacrylate was added in the preparation of a porous starch with high oil absorption rate, and the remaining steps and parameters were the same.

[0056] Comparative Example 9

[0057] Compared with Example 2, 0.4 parts by weight of thiourea oxide was added in the preparation of a porous starch with high oil absorption rate, and the other steps and parameters were the same.

[0058] Comparative Example 10

[0059] Compared with Example 2, 0.9 parts by weight of thiourea oxide was added in the preparation of a porous starch with high oil absorption rate, and the other steps and parameters were the same.

[0060] Comparative Example 11

[0061] Compared with Example 2, the amount of hydrogen peroxide solution added in the preparation of a porous starch with high oil absorption rate is 0.01 parts by weight, and the other steps and parameters are the same.

[0062] Comparative Example 12

[0063] Compared with Example 2, the amount of hydrogen peroxide solution added in the preparation of a porous starch with high oil absorption rate is 0.04 parts by weight, and the remaining steps and parameters are the same.

[0064] Performance Testing

[0065] (1) Add the sample to a pycnometer with a known weight W0, tap the pycnometer gently, vibrate and compact until the bottle mouth, gently scrape it flat with a glass plate, weigh it, and continue compacting until the weight difference before and after does not exceed 0.01g. Accurately weigh the weight W1 of the pycnometer and the sample, add distilled water to the same pycnometer until the bottle mouth, scrape it flat, and measure the total weight W2. The calculation formula is as follows:

[0066]

[0067] Where: ρ is the density of distilled water

[0068] The bulk density of the porous starch with high oil absorption rate prepared in Examples 1-3 and Comparative Examples 1-6 was tested by this method. The results are shown in Table 1.

[0069] (2) Accurately weigh porous starch and add 25% distilled water to prepare 2% starch emulsion, and use a digital constant temperature water bath pot of model HH-2 to maintain a constant temperature of 85°C for magnetic stirring. Keep the temperature for 30 minutes and keep stirring. Take out and naturally cool to room temperature. Accurately pipette 10% uniform paste into a graduated test tube. After natural sedimentation for 24 hours, read the volume V of the sediment, which is the sedimentation area of ​​the starch solution. The sedimentation area test of the porous starch with high oil absorption rate prepared in Examples 1-3 and Comparative Examples 1-6 is performed, and the results are shown in Table 1.

[0070] (3) Weigh the porous starch (m1) accurately in a 100-ml conical flask, add an appropriate amount of soybean salad oil (distilled water), stir at 35 °C for 4 h, and then place it in a sand core funnel (m0) of known mass for suction filtration until no oil droplets (liquid droplets) drip. Weigh the total mass of the sand core funnel and the porous starch (m2), and calculate the oil absorption rate (water absorption rate) A. The calculation formula is as follows:

[0071]

[0072] The oil absorption rate of the porous starch with high oil absorption rate prepared in Examples 1-3 and Comparative Examples 7-12 was tested by this method. The results are shown in Table 2.

[0073] (4) Grafting rate refers to the ratio of the mass of grafted monomer in the grafted porous starch after extraction to the mass of the original porous starch. The grafting rate is calculated by weighing the mass of the grafted porous starch after extraction and the mass of the original porous starch. The calculation formula is as follows:

[0074]

[0075] The grafting rate of the porous starch with high oil absorption rate prepared in Examples 1-3 and Comparative Examples 7-12 was calculated in this way. The results are shown in Table 2.

[0076] (5) During the grafting reaction, a portion of the monomers are not grafted onto the porous starch molecules after polymerization, which is called homopolymer; the other portion is polymerized into high molecular weight chains and grafted onto the porous starch matrix. The grafting efficiency indicates the mass fraction of the monomers grafted onto the matrix to the monomers participating in the reaction. The greater the grafting efficiency, the less homopolymer there is and the better the grafting effect. The calculation formula is as follows:

[0077]

[0078] The grafting efficiency of the porous starch with high oil absorption rate prepared in Examples 1-3 and Comparative Examples 7-12 was calculated. The results are shown in Table 2.

[0079] Table 1

[0080] Bulk density (g / mL) Sedimentation volume (mL) Example 1 0.437 2.4 Example 2 0.426 2.1 Example 3 0.443 2.6 Comparative Example 1 0.735 5.9 Comparative Example 2 0.740 5.3 Comparative Example 3 0.753 5.7 Comparative Example 4 0.729 5.5 Comparative Example 5 0.586 6.9 Comparative Example 6 0.594 7.2

[0081] Table 2

[0082]

[0083]

[0084] The degree of cross-linking of cross-linked starch is difficult to measure directly, so it is generally characterized by indirect indicators. Studies have shown that the sedimentation volume of starch is inversely proportional to the degree of cross-linking. The higher the degree of cross-linking of starch, the smaller the sedimentation volume. As shown in Table 1, the powder of the present invention uses a composite enzyme of saccharifying enzyme: β-amylase = 2:1, so that porous starch produces a large number of holes that penetrate from the surface to the center of the particle, and channels are formed inside the starch particles, which have a large specific surface area and a high porosity, thereby reducing the bulk density; sodium trimetaphosphate is used as a cross-linking agent, and sodium trimetaphosphate is cross-linked with the porous starch after enzymolysis, the molecular chain is broken, and more hydroxyl groups are exposed to form a network structure, which enhances the strength of hydrogen bonds and inhibits the swelling of cross-linked porous starch particles, thereby reducing the sedimentation volume.

[0085] As shown in Table 2, the present invention adds ethyl methacrylate, sodium trimetaphosphate and a network structure formed by the enzymatically hydrolyzed porous starch. The surface of the porous starch particles and the strong adsorption force of the porous starch particles absorb the ethyl methacrylate into the particles, and the porous starch is closely combined with the porous starch for grafting, which has higher stability and is not easy to separate, further improving the adsorption capacity and increasing the oil absorption rate; hydrogen peroxide is used as an initiator of the reaction system to generate free radicals, which trigger the graft copolymerization of the porous starch and the ethyl methacrylate, generate a large number of active centers, and polymerization starts from the active centers, so that the monomers are smoothly grafted onto the porous starch to generate branches, which greatly improves the grafting rate; thiourea oxide forms a reduction system with ferrous ions, reduces the trivalent iron ions generated in the system to divalent iron ions, re-participates in the reaction, and increases the free radical concentration in the reaction system. On the other hand, it can also generate free radicals to participate in the reaction, which quickly improves the grafting rate.

[0086] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing porous starch with high oil absorption rate, characterized in that: The method comprises the following steps: weighing a cross-linked body, sequentially adding 0.1 mol / L ammonium ferrous sulfate solution, deionized water, ethyl methacrylate, oxidized thiourea and 0.003 mol / L hydrogen peroxide solution, controlling the rotation speed, mechanically stirring evenly, passing nitrogen for 0.5-1h, controlling the temperature for reaction, washing with water after the reaction is completed to obtain a grafted porous starch, placing the grafted porous starch in an extractor for acetone extraction for 24-26h, taking out and drying to obtain a porous starch with high oil absorption rate; The weight ratio of the crosslinked body, ammonium ferrous sulfate solution, deionized water, ethyl methacrylate, oxidized thiourea and hydrogen peroxide solution is 4-6: 0.03-0.05: 130-160: 8-9: 0.5-0.8: 0.02-0.03; The crosslinked body is prepared by the following method: Step S1, stirring and mixing wheat starch and a buffer solution to obtain a mixed solution, preheating, adding a composite enzyme, stirring and enzymolyzing under controlled temperature, adding hydrochloric acid to adjust the pH to 3 after the reaction is completed, mechanically stirring and mixing to react, neutralizing the hydrochloric acid in the solution with NaOH after the reaction is completed, vacuum filtering after the neutralization is completed, washing with ethanol and water, and drying at normal pressure to obtain enzymolyzed starch; The dosage ratio of the wheat starch, buffer and complex enzyme is 30-60 g: 170-190 mL: 3-5 g; the buffer is sodium dihydrogen phosphate-citric acid with a pH of 6.0, and the complex enzyme is saccharifying enzyme: β-amylase = 2:1; Step S2, mixing the enzymatic starch obtained in step S1, deionized water and sodium sulfate, adjusting the pH to 11 with sodium hydroxide, stirring in a water bath, adding sodium trimetaphosphate for mixed reaction, adjusting the pH to 6 with hydrochloric acid, washing with water, drying and crushing to obtain a cross-linked body; The dosage ratio of the enzymatic starch, deionized water, sodium sulfate and sodium trimetaphosphate is 20-40g: 100-120mL: 12-16g: 2-4g.

2. The method for preparing porous starch with high oil absorption rate according to claim 1, characterized in that: The rotation speed is 30-50 rpm, the temperature is 48-52° C., and the reaction time is 1-1.2 h.

3. The method for preparing porous starch with high oil absorption rate according to claim 1, characterized in that: The extractor is a Soxhlet extractor.

4. The method for preparing porous starch with high oil absorption rate according to claim 1, characterized in that: The preheating environment in step S1 is preheating in a water bath at 47-51°C for 9-13 minutes, the temperature of enzymatic hydrolysis stirring is 47-51°C, the reaction time is 10-15 minutes, and the temperature of atmospheric pressure drying is 35-45°C, and the time is 22-26 hours.

5. The method for preparing porous starch with high oil absorption rate according to claim 1, characterized in that: The water bath stirring temperature in step S2 is 42-48° C., and the mixing reaction time is 1-1.5 h.

Citation Information

Patent Citations

  • Preparation method of cassava starch type high-water absorbency and oil-oil absorbency resin by cross-linked grafting technology

    CN102887978A

  • Preparation method of high-polymer flocculatant EA-g-SA (ethyl acrylate-g-succinic anhydride) esterificaiton-oxidation cassava starch

    CN107522819A

Cited By

  • Porous starch with high adsorption capacity and preparation method thereof

    CN122344605A